Hubungan Supervisi Keperawatan Dengan Pelaksanaan Budaya Safety di RSUD Dr. M. Haulussy Ambon - Jotlely, Hery; Matulessy, Elisabeth; Lameky, Vernando Yanry (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Nursing supervision is important in improving the quality of service and hospital patient safety culture. This study analyzes the relationship between nursing supervision and implementing a safety culture at Dr. M. Haulussy Ambon Regional Hospital. Using a quantitative descriptive research design with a cross-sectional approach, this study involved 70 nurses selected through a total sampling method. Data were collected using a questionnaire and analyzed using the Chi-Square test. The results showed a significant relationship between nursing supervision and patient safety culture (p = 0.002). Nurses who received good supervision tended to comply more with patient safety procedures. This finding confirms that adequate nursing supervision can improve patient safety culture and reduce the risk of medical incidents in hospitals. Therefore, improving a more structured, technology-based supervision system is recommended to ensure optimal service quality. Keywords: Nursing Supervision, Patient Safety Culture, Hospital, Service Quality